KEMAMPUAN MEMANGSA DOLICHODERUS THORACICUS SMITH (HYMENOPTERA : FORMICIDAE) PADA BERBAGAI STADIUM PERKEMBANGAN SERANGGA PENGGEREK BUAH KAKAO, CONOPOMORPHA CRAMERELLA (SNELLEN) - Edy Edy; Alam Anshary; Moh. Yunus (Universitas Tadulako, 2008)
This research aim to know the ability imago D. thoracicus to prey C. cramerella at various growth stadium. This research in executing at April, 2007 up to August, 2007 in Pest Laboratory and Entomological Faculty Of Agriculture of University Tadulako. Research designed in Complete Random Device (RAL), consisted of by four treatment and three replication. As for treatment is gift prey the : P1 ( egg C. cramerella), P2 (final larva instars C. cramerella), P3 (Pupa C. cramerella), P4 (egg mixture, larva, pupa C. cramerella). Result of research indicate that the ability prey D. thoracicus to prey C. cramerella larva stadium is highest comparing treatment of egg and pupa, same thing became of by the mixture treatment (egg, larva, pupa). Along of amount which is prey by D. thoracicus highest at larva treatment that is 2.33 - 8.33 so that big possibility of larva stadium is appropriate prey for D. thoracicus.